The Abandoned Stakeholders: Pharmaceutical Companies and Research Participants - Chang, Pepe Lee (Journal of business ethics, 2017)
Most discussions concerned with advancing the just and ethical treatment of research participants in developing countries have revolved around the moral principle of autonomy and the legal doctrine of informed consent (O’Neill 2002). However, if emerging ethical concerns are to be addressed effectively, the discussion needs to expand into the domain of business ethics where arguments addressing issues such as fair/appropriate compensation, entitlement, and corporate obligations to stakeholders are commonplace. The argument I present in this paper will conclude that emerging ethical considerations regarding the treatment of research participants in developing countries have evolved well beyond the scope of the principle of informed consent and that in order to resolve these concerns more appropriately and effectively, the new default or status quo should be to consider research participants as stakeholders of the sponsoring pharmaceutical company, even after the clinical trial is completed. This conclusion is significant because although it is fair to assume that, at some point in the timeline, most stakeholder theorists already do consider research participants stakeholders of the pharmaceutical company sponsoring the trial, the completion date of the clinical trial usually signifies and marks the termination of their stakeholder status and thus any consideration of what is owed further to the research participant.